2017
DOI: 10.1002/mp.12688
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a hybrid Monte Carlo‐Pencil Beam dose algorithm for proton therapy inverse planning

Abstract: The hybrid algorithm provides an improved trade-off between accuracy and speed. This algorithm can be immediately considered as an option for improving dose calculation accuracy of commercial analytical treatment planning systems, without a significant increase in the computation time (≪5 min) with respect to current PB-based optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
(84 reference statements)
0
12
0
Order By: Relevance
“…For this case, we generated a new plan using the MCsquare-based optimizer, MIROpt. 33 From the DVH in the Fig. 7, it can be observed that the dose recalculated by MCsquare reflects significant degradation of D95 by 6.8% and of the HI index by 6.0% compared to what the ADC would indicate.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…For this case, we generated a new plan using the MCsquare-based optimizer, MIROpt. 33 From the DVH in the Fig. 7, it can be observed that the dose recalculated by MCsquare reflects significant degradation of D95 by 6.8% and of the HI index by 6.0% compared to what the ADC would indicate.…”
Section: Discussionmentioning
confidence: 93%
“…. For this case, we generated a new plan using the MCsquare‐based optimizer, MIROpt . From the DVH in the Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The robustness test presented in this paper is applied to a patient case in order to illustrate the feasibility of this concept. The MIROpt 4D robust optimizer, developed in house and based on MCsquare dose calculation, was employed to generate a treatment plan for a lung tumor patient. A robust plan was optimized on the clinical target volume (CTV) based on the 4DCT series composed of 10 CT phases.…”
Section: Methodsmentioning
confidence: 99%